Investigation of surface metal matrix composites of reinforced aluminium alloy produced using friction stir processing - Che Dini Marini, Che Mohammad Ishkandar El-Rahimin (2020)
Aluminium alloy demonstrates promising excellent properties in many applications. However, aluminium alloy exhibits poor tribological behaviour in some extends. Studies have developed for surface modifications of aluminium alloy in order to alter the surface properties while maintaining the properties of the core. Fusion route and casting methods have been developed to improve the surface properties of aluminium alloy. However, these methods deal with high temperatures that lead to poor wettability of ceramic particle during the process. This research is aimed to investigate the surface modification of aluminium alloy, AA6061 using friction stir processing (FSP). The surface modification of was done on non-reinforced aluminium alloy and reinforced aluminium alloy, namely FSPed AA6061 and FSPed AA6061/RHA, respectively. Rice husk ash (RHA) was used as reinforced material with composition of 6 vol.% . RHA is a ceramic particle which contains high level of silica (SiO2). In this research, FSP was performed at a constant travel speed of 25 mm/min and different rotation speeds were varied at 1000, 1200, 1400, 1500 and 1600 rpm using a probe cylindrical tool. FSP was used as an approach to refine and enhance the mechanical properties and the tribological behaviour of AA6061. A microscopic examination was done using an optical microscope (OM) and revealed that FSP refined the grain size and the reinforced material is successfully held within the alloy. The mechanical properties of the alloys particularly the microhardness, were tested and compared. The average microhardness value decreased as the FSP rotational speed recorded for both FSPed AA6061 and FSPed AA6061/RHA were increased. However, by using FSP, the mechanical properties of FSPed AA6061 and FSPed AA6061/RHA have improved compared to AA6061. This significance was due to grain refinement of AA6061 and the presence of RHA within the AA6061. It was found that wear behaviour has improved for FSPed AA6061/RHA compared to FSPed AA6061 followed by AA6061. Meanwhile, observation under a scanning electron microscope (SEM) has found that the wear mechanism changed from adhesive wear to abrasive wear. Furthermore, based on the energy-dispersive X-ray spectroscopy (EDX) remark, the presence of RHA within the AA6061 proved that RHA helps to improve the mechanical and wear behaviour of FSPed AA6061 followed by AA6061 itself.